PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN DENGAN MENGGUNAKAN TALKING STICK DI KELAS IV SDN 37 KOTO PULAI - darefni, muspita; Taufik, Taufina; Zainarlis, Zainarlis (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
AbstrackThis research is motivated by the low skill of students in reading comprehension in class IV Elementary.This research is a classroom action research (PTK) which uses qualitative and quantitative approach.This result of this study indicate an increase in : (a) pre-cycle stage of cycle I 66,2 (b) the reading stage 65. (c) the post-cycle60,cyle II (a) pre-cyle stage 85,5(b) the reading stage 90 (c) the post-cyle 79.Based on the results of this study can be concluded that by using the Talking Stick can improve the skills of reading comprehension of sixth grade students SDN 37 Koto Pulai. Keyword : Reading Comprehension, Talking Stick